Cubosomes In Transdermal Drug Delivery: Advances, Challenges, And Future Perspectives - Ahmed A, Syed Asad; S, Jeganath; S, Kanna (Journal of Neonatal Surgery, 2025)
Cubosomes, nanostructured lipid particles, have developed into effective carriers in transdermal drug delivery due to their unique bicontinuous cubic phase structure. These particles offer several advantages, including high drug loading capacity, stability, and the ability to encapsulate both hydrophilic and hydrophobic drugs, making them suitable for a wide range of therapeutic applications. This review explores the latest advancements in cubosome-based transdermal drug delivery systems (TDDS), including their mechanisms of skin penetration, sustained release profiles, and targeted delivery capabilities. The challenges faced in cubosome formulations, such as stability issues, drug leakage, and scaling up manufacturing processes, are also discussed. Furthermore, future perspectives on improving cubosome performance through hybrid systems, smart drug delivery, and personalized medicine are explored. This review provides a comprehensive overview of the current state of cubosomes in transdermal drug delivery and their potential for revolutionizing the field of topical therapeutics